Biomarker as an Indicator of River Water Quality Degradation - Dwina Roosmini; Indah Rachmatiah; Suharyanto Suharyanto; Agus Soedomo; Fajar Hadisantosa (Institute for Research and Community Services, Institut Teknologi Bandung, 2006)
Generally physical and chemical methods are use in river water quality monitoring; currently biomarker is developed as alternative biomonitoring method. The aim of this study is to look at the probability using aquatic species in monitoring river water pollutants exposure. This study was done by using Hyposarcus pardalis as biomarker to analyze river water quality in Upstream Citarum River. Hyposarcus pardalis were taken along the river at five sampling point and look at the Cu and Zn concentration. Results from this study show that there was an indication that river water quality has been degrading along the river from upstream to downstream. Zn concentration in Hyposarcus pardalis were increasing as well as Cu concentration. The increase of Zn concentration in Hyposarcus pardalis indicating that the river was polluted by Zn. Secondary data and observation at sampling location shown that textile was the dominant industry which may contribute the Zn concentration in river as they received the effluent. Cu is use in metal coating process, as well as textile industry metal industries were identified at Majalaya, Bantar Panjang, Dayeuh Kolot and Katapang in Bandung-Indonesia. As a receiving water from many activities along the river, upstream Citarum River water quality become degrading as the increasing of heavy metal Zn and Cu concentration in Hyposarcus pardalis.